1987
DOI: 10.1128/aem.53.4.704-707.1987
|View full text |Cite
|
Sign up to set email alerts
|

A new method to determine Giardia cyst viability: correlation of fluorescein diacetate and propidium iodide staining with animal infectivity

Abstract: The viability of Giardia muris cysts was studied with the fluorogenic dyes fluorescein diacetate (FDA) and propidium iodide (PI). G. muris cysts were seen to fluoresce intensely green with FDA at an excitation wavelength of 450 to 490 nm. Cysts stained with PI fluoresced bright orange at an excitation wavelength of 450 to 490 nm and bright red at 545 to 546 nm. Examination of isolated G. muris cyst preparations stained with FDA-PI revealed that greater than 85% of the cysts stained green with FDA and less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 20 publications
0
41
0
2
Order By: Relevance
“…It has been demonstrated that the desaturation of membrane lipids is essential to low temperature tolerance in cyanobacteria. The desaturation of fatty acids occurs without de novo synthesis of fatty acids during low temperature acclimation of cyanobacterial cells (Singh et al 2002) through acylase, which has been implicated in the hydrolysis of FDA (Schupp & Erlandsen 1987). Second, substances that include nucleophilic and basic amino acids, including histidine and cysteine, have been reported to induce abiotic cleavage of FDA (Clarke et al 2001;Wanandy et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the desaturation of membrane lipids is essential to low temperature tolerance in cyanobacteria. The desaturation of fatty acids occurs without de novo synthesis of fatty acids during low temperature acclimation of cyanobacterial cells (Singh et al 2002) through acylase, which has been implicated in the hydrolysis of FDA (Schupp & Erlandsen 1987). Second, substances that include nucleophilic and basic amino acids, including histidine and cysteine, have been reported to induce abiotic cleavage of FDA (Clarke et al 2001;Wanandy et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cyst viability may be assessed using differential interference contrast (DIC) microscopy and vital dye assays. The uptake of the vital dye, propidium iodide, by cysts has been shown to correlate with the inability to excyst and infect animals (Schupp and Erlandsen, 1987). Nonetheless, viability assessment based on vital dye inclusion or exclusion is considered only an estimate of infectivity.…”
Section: Introductionmentioning
confidence: 99%
“…and Giardia spp. (Campbell, Robertson, and Smith 1992;Foster et al 2003;Kato and Bowman 2002;Medema et al 1998;Schupp and Erlandsen 1987;Vesey et al 1994; see also Quintero-Betancourt, Peele, and Rose 2002 for review), and of intra-erythrocytic protozoans, such as Plasmodium falciparum (Srivastava, Rottenberg, and Vaidya 1997), Babesia bovis (Wyatt, Goff, and Davis 1991), Leishmania amazonensis (Bertho, Cysne, and Coutinho 1992;Guinet et al 2000), and Theileria sergenti (Yagi et al 2000).…”
mentioning
confidence: 99%